PLN Organizational Leaders Manajemen Talent sebagai Strategi Pengelolaan Human Capital - Musthofa Musthofa (KILAT, 2020)
The high demands of customers on the reliability of the quality of electric power to the government's efforts to meet electricity needs through the 35,000 MW Program pose a serious challenge to PLN. The crucial condition of the distribution section is the spearhead of PLN in preparing leaders who understand the culture and business challenges. PLN has not used a character approach to place employees according to the Type of Position that has different job demands and characters. The problems faced by PLN in implementing talent management, the difficulty in determining talent in the right position (the right man in the right place) with the target of preparing future leaders 25% of the total 49,100 employees to PLN as an Organizational Leader. The PESTEL Analysis method that considers strategic issues and critical success factors (CSF) generated Talent Profile Data with personality preferences measured by MBTI and DISC test kits. The purpose of this study is to create a Business Unit Character Profile and Talent Personality Profile. The results of the study formed the personal character of talent 140 employees or 68% of the talent pool, Character Model Work units have been classified from external challenges in the work unit and issued a decree mutation promotion of top supervisors and basic managers 33 people who went up and 48 people up the level of the organization. Impacted performance improvement PLN East Java Distribution achieved the best performance (94.1) and NKO Value 95.0 in 2017.